Sex-dependent differential transcript expression in the placenta of growth restricted infants. (October 2022) - O'Callaghan, Jessica L.; Clifton, Vicki L.; Prentis, Peter; Ewing, Adam; Saif, Zarqa; Pelzer, Elise S.
Abstract: Introduction: The pathological decrease of fetal growth during gestation can lead to subsequent poor health outcomes for the fetus. This process is commonly controlled by the placenta, the interface between mother and baby during gestation. Sex-specific gene expression has been implicated in placental function, therefore, there is a need to determine if it is important during reduced fetal growth. We therefore aimed to characterise placental gene expression at term to evaluate sex-specific genetic changes that occur in small for gestational age (SGA) infants. Methods: RNA-sequencing of twelve human placental tissue samples collected from pregnancies yielding either term appropriate for gestational age (AGA) or SGA infants identified at delivery. Candidate genes associated with fetal size and fetal sex were identified using differential gene expression and weighted gene co-expression network analyses. Single-cell sequencing data was used for candidate validation and to estimate candidate transcript expression in specific placental cell populations. Results: Differential gene expression and weighted gene co-expression network analyses identified 403 candidate transcripts associated with SGA infants. One hundred and three of these transcripts showed sex-specific expression. . Published placental sequencing datasets were used to validate the key expression results from the twelve placental samples initially studied; the sex-independent transcript expression for genes involved in cell cycle processes in males (7 transcripts) and endoplasmic reticulum stress in females (17 transcripts). Discussion: This study identified the activation of multiple molecular mechanisms involved in the placental response to an adverse environmental stressor. Mechanisms such as disrupted protein synthesis were shared between infant biological sex when comparing AGA to SGA, whilst other pathways such as cell cycle and endoplasmic reticulum stress appear as independent/specific to either males or females when investigating reduced fetal growth. This data suggests that sexual dimorphism is an important consideration when examining placental dysfunction and poor fetal growth. Highlights: Placental transcript expression is divergent dependent on fetal size and sex. Sex-independent expression of genes involved in protein synthesis are correlated to fetal size. After stratifying for fetal sex, there were sex dependent placental transcriptome changes related to fetal size. Genes involved in cell cycle processes were identified in the male only analyses. For the analysis restricted to only female infants, genes were involved in the endoplasmic reticulum.